1994
DOI: 10.1105/tpc.6.9.1253
|View full text |Cite
|
Sign up to set email alerts
|

Control of leaf and chloroplast development by the Arabidopsis gene pale cress.

Abstract: Leaf plastids of the Arabidopsis pale cress (pac) mutant do not develop beyond the initial stages of differentiation from proplastids or etioplasts and contain only low levels of chlorophylls and carotenoids. Early in development, the epidermis and mesophyll of pac leaves resemble those of wild-type plants. In later stages, mutant leaves have enlarged intercellular spaces, and the palisade layer of the mesophyll can no longer be distinguished. To study the molecular basis of this phenotype, we cloned PAC and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 26 publications
(28 reference statements)
6
73
0
Order By: Relevance
“…We have observed that the mesophyll tissue of cla1-1 is altered in comparison with wild-type plants. Similar phenotypes have been reported in other mutants that affect chloroplast development at an early stage such as Dcl-m and GHOST in tomato, Dag in Antirrhinum (Scolnik et al, 1987;Chatterjee et al, 1996;Keddie et al, 1996), and PAC and ATD in Arabidopsis (Reiter et al, 1994;van der Graaff, 1997). The common denominator in all is that the plastids are arrested early in development.…”
Section: Discussionsupporting
confidence: 51%
“…We have observed that the mesophyll tissue of cla1-1 is altered in comparison with wild-type plants. Similar phenotypes have been reported in other mutants that affect chloroplast development at an early stage such as Dcl-m and GHOST in tomato, Dag in Antirrhinum (Scolnik et al, 1987;Chatterjee et al, 1996;Keddie et al, 1996), and PAC and ATD in Arabidopsis (Reiter et al, 1994;van der Graaff, 1997). The common denominator in all is that the plastids are arrested early in development.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies using mutants (Reiter et al, 1994) and antisense transgenic plants (Flachmann et al, 1995) have revealed that the level of CAB mRNA does not necessarily correlate with the level of LHCP (light-harvesting chlorophyll proteins encoded by CAB). We investigated whether the reduced CAB mRNA levels in the cuel mutant were reflected by a similar reduction of LHCP.…”
Section: Cue? Mutations Reduce the Expression Of Light-regulated Genementioning
confidence: 99%
“…The dag mutant from Antirrhinum (Chatterjee et al, 1996) and dcl1 from tomato (Keddie et al, 1996) do not contain chloroplasts but rather plastids resembling nondifferentiated proplastids. These genes together with the PALE CRESS gene from Arabidopsis (Reiter et al, 1994) affect both chloroplast development and leaf architecture.…”
Section: Introductionmentioning
confidence: 99%
“…The dag mutant from Antirrhinum (Chatterjee et al, 1996) and dcl1 from tomato (Keddie et al, 1996) do not contain chloroplasts but rather plastids resembling nondifferentiated proplastids. These genes together with the PALE CRESS gene from Arabidopsis (Reiter et al, 1994) affect both chloroplast development and leaf architecture.One class of mutations gives rise to variegated plants that have a mutant phenotype in some sectors and a wild-type phenotype in others. The iojap (Han et al, 1992) mutant of maize or the chloroplast mutator in maize and Arabidopsis (Martínez-Zapater et al, 1992) all have a variegated albino phenotype similar to heteroplastid tobacco plants created after selection for chloroplast mutations.…”
mentioning
confidence: 99%